Abductive Analysis, theorizing qualitative research - Garcés Vélastegui, Pablo (2017)
Review of the book by Iddo Tavoty and Stefan Timmermans, Abductive Analysis, theorizing qualitative research, Chicago: University of Chicago Press, 2014.